Electrocatalytic effect of recombinant Mn peroxidase from corn on microbiosensors to detect glucose. (August 2022) - Izadyar, Anahita; Van, My Ni; Miranda, Marcela; Weatherford, Scout; Hood, Elizabeth E.
Abstract: Our previous studies revealed that a recombinant enzyme from corn is effective and suitable for glucose monitoring. However, the challenge is to further extend our previous work by modification of a 10 μm diameter gold microelectrode, (GME), which guides this biosensor towards practical applications and in vivo analytical monitoring of glucose. The polyaniline (PANI) - gold nanoparticles (GNPs)- glucose oxidase (GOX )- plant-produced manganese peroxidase (PPMP)/GME composition showed excellent chronoamperometric (CA) response for the selective and sensitive enzymatic detection of glucose. PANI - GNPs- GOX- PPMP/GME exhibits a wide linear range of 0.001–16.0 mM, and a lower detection limit of 0.50 μM when applying CA. Linear sweep voltammetry (LSV) and cyclic voltammetry (CV) were also applied for further electrochemical characterization of the modified microelectrode to detect glucose. The biosensor selectivity was assessed by determining glucose concentrations in the presence of ascorbic acid, dopamine, aspartame, fructose, uric acid, caffeine, and 10% diet coke. As a result, the new dual enzyme microbiosensor is proposed as a tool that facilitates medical diagnosis and monitoring of glucose levels of foods. Graphical abstract: Schematic illustration of the PANI- GOX- PPMP/GNE electrode and LSVs response.Color code: AuNPs, golden yellow; PANI, green; PPMP, red; GOx, brown. Image 1 Highlights: Effect of enzymes produced from an agricultural crop. Using conductive polymers (CPs) in this biosensor construction to stabilize the membrane. Advent devices for various applications such as drug discovery, disease diagnosis, biomedicine, food safety and processing, environmental monitoring, defense and security.